The patient's voice: Patient involvement in medical product regulation. (March 2016) - von Tigerstrom, Barbara
Authorities responsible for regulating medicines and other medical products continue to expand opportunities for direct participation of patients and their representatives in regulatory processes. For example, patient representatives can participate as members of scientific committees and provide input in various ways. This article examines the current framework and recent initiatives for such participation in the US Food and Drug Administration and European Medicines Agency. It draws from scholarship on public and patient participation in other contexts to describe and clarify the purposes and roles of patient involvement and to identify issues needing attention in the development of these initiatives, including systemic factors that may impede the ability of patient representatives to fulfill their roles effectively. It also considers convergent efforts to engage patients in research and development that could alleviate some of these difficulties and provide an opportunity to rethink the goals and methods of patient involvement in a larger context.